Economic impacts of developing a biofuel industry in Mozambique - Faaiqa Hartley; Dirk Ernst van Seventer; Emilio Tost\~ao; Channing Arndt (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
Mozambique is one of the most promising African countries for producing biofuels and the national biofuel policy of 2009 identifies measures to incentivize biofuel production. Demand for biofuels in the Southern African Development Community is expected to increase over the next few years as 7 of its 15 member states have implemented or proposed the implementation of blending mandates by 2020. South Africa is one of these countries. Using a dynamic recursive computable general equilibrium (CGE) model, we estimate the impacts of expanding biofuel production in Mozambique under both commercial and smallholder-type farming models, including and excluding bagasse cogeneration.
Keywords: C68; Q16; Q18; 330; biofuel; computable general equilibrium; food security; Mozambique